1989
DOI: 10.1042/bj2610531
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic glutathione transferases from rat liver. Primary structure of class alpha glutathione transferase 8-8 and characterization of low-abundance class Mu glutathione transferases

Abstract: Six GSH transferases with neutral/acidic isoelectric points were purified from the cytosol fraction of rat liver. Four transferases are class Mu enzymes related to the previously characterized GSH transferases 3-3, 4-4 and 6-6, as judged by structural and enzymic properties. Two additional GSH transferases are distinguished by high specific activities with 4-hydroxyalk-2-enals, toxic products of lipid peroxidation. The most abundant of these two enzymes, GSH transferase 8-8, a class Alpha enzyme, has earlier b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 50 publications
3
37
0
1
Order By: Relevance
“…However, the total activity of GSTs in the liver did not differ significantly between the control and DHA-fed groups (Table 2). Ålin et al [34] and Hiratsuka et al [35] reported that GSTA4-4, which present as a very minor GST protein in rat liver, exhibited extremely high catalytic activity towards 4-HNE. When GSTs in rat liver were separated by the chromatography on DEAE-cellulose column, GST A4-4 (also called GST 8-8) activity (60 µmol/min) was much lower than other GSTs activity (4460 µmol/min) [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the total activity of GSTs in the liver did not differ significantly between the control and DHA-fed groups (Table 2). Ålin et al [34] and Hiratsuka et al [35] reported that GSTA4-4, which present as a very minor GST protein in rat liver, exhibited extremely high catalytic activity towards 4-HNE. When GSTs in rat liver were separated by the chromatography on DEAE-cellulose column, GST A4-4 (also called GST 8-8) activity (60 µmol/min) was much lower than other GSTs activity (4460 µmol/min) [34].…”
Section: Discussionmentioning
confidence: 99%
“…Ålin et al [34] and Hiratsuka et al [35] reported that GSTA4-4, which present as a very minor GST protein in rat liver, exhibited extremely high catalytic activity towards 4-HNE. When GSTs in rat liver were separated by the chromatography on DEAE-cellulose column, GST A4-4 (also called GST 8-8) activity (60 µmol/min) was much lower than other GSTs activity (4460 µmol/min) [34]. Accordingly, even if the total activity of GSTs does not change in rats fed DHA, GSTs could be associated with the excretion of lipid peroxidation-derived reactive aldehydes including 4-HNE and even 4-HHE.…”
Section: Discussionmentioning
confidence: 99%
“…Although N-terminal amino acid sequence analysis was performed with a gas-phase protein sequencer, the Nterminal amino acid residue of this form, like that of subunit 1, was blocked. Alin et al [28] have recently reported that liver GST 8-8 of the class Alpha is also Nterminally blocked. The subunit Mr of the pl 5.8 form is similar to that of subunit 10 (Yfetus) [13], but the latter form has a very basic pl (9.8) [6,13] and a high activity towards cumene hydroperoxide.…”
Section: Discussionmentioning
confidence: 99%
“…These results indic#te that the Ys subunit differs from subunits 8 and 10. Alin et al [28] have described the acidic form designated GST A(6), with high activities towards 4-hydroxynon-2-enal and trans-4-phenylbut-3-en-2-one. Although it is not clear yet whether GST A(6) belongs to the class Alpha or not, its substrate-specificity is different from that of the spleen pl 5.8 form.…”
Section: Discussionmentioning
confidence: 99%
“…among GSTs, by detoxifying racemic HNE [20]. GSTA4-4 orthologues, occurring as minor enzymes in liver cytosol of mice [9] and humans [10], also exhibit extremely high catalytic activity in the conjugation and detoxification of racemic HNE compared with other Alpha-class GSTs and GST isoforms of other classes [17].…”
Section: Introductionmentioning
confidence: 99%